A Description of the Use of Sildenafil in the Paediatric Intensive Care Unit at Red Cross War Memorial Children's Hospital - El-Boraei, Samah (Department of Paediatrics and Child Health, 2025)
Background. The clinical profiles of African children with pulmonary hypertension (PH) are largely unknown. Sildenafil is the only available oral treatment for PH in South Africa (SA) and is widely used, mostly off-label, despite little evidence for safety or efficacy. Objectives. To describe the use of sildenafil in the Paediatric Intensive Care Unit (PICU) at Red Cross War Memorial Children's Hospital (RCWMCH), to provide insights into the clinical profiles and outcomes of children with PH Methods. A retrospective descriptive study of all children treated with sildenafil in the PICU between 1 January 2017 and 31 December 2019. Results. 108 patients in 162 PICU admissions were included (median age 5 months; 54.6% male), accounting for 4.1% of all PICU admissions during the study period. Most patients (n=92, 85.2%) had congenital heart disease (CHD), which was associated with survival on univariate analysis (p=0.009). The majority (n=37, 34.3%) were classified as World Health Organisation PH Classification Group 1: Pulmonary Arterial Hypertension. Sildenafil was initiated in PICU in 98 (72.1%) cases and for inhaled nitic oxide (iNO) weaning in 56 (57.1%). For most patients, sildenafil was continued after PICU (n=104, 76.5%) and hospital (n=66, 48.5%) discharge. The three-year survival rate was 75.9 % (n=82). Conclusions. In our PICU population, sildenafil is used predominantly for CHD related PH. Sildenafil is used to facilitate iNO weaning and is frequently continued long-term after hospital discharge. Survival rates were acceptable. Research is needed to determine the true prevalence of PH and the safety profile of sildenafil in SA.